Controle de qualidade em espectroscopia de prótons por ressonância magnética - Olimpio, Aline Beatriz (2019)
This study presents the development of a quality control routine for proton magnetic resonance spectroscopy performed on the Siemens Avanto Fit 1,5 T equipment. The objective of this study is to evaluate the repeatability of the system in the acquisition of single and multi voxel spectroscopy, using the STEAM (Stimulated Echo Acquisition Mode) and SE (spin echo) techniques, also called PRESS (Point Resolved Spectroscopy), analyzing data from two metabolites: Acetate and Lactate, in relation to peak amplitude and integral below the peak area, for short and long echo times. The phantom D170 Spectroscopy was positioned on the 18-channel head matrix radio frequency coil, the manufacturer's quality control protocol was used. A total of 15 samples were obtained on two different dates, being 8 samples on the first day, a 30 day interval and 7 samples on the second day, after the preventive maintenance of the equipment, ensuring that the other parameters are within the normal range. The information was collected, the data tabulated and analyzed graphically. The test of homogeneity of the magnetic field had results below the values established by the regulatory standards, which guarantees the accuracy in the identification of the peak of frequency of the water, for later application of the technique of water suppression. It was observed that the SE / PRESS technique was more advantageous because it has a higher signal-to-noise ratio, but the STEAM technique may be preferable in noncollaborative patients. From the established methodology, since the manufacturer does not provide reference values, the repeatability test was applied so that the spectral quality control was acquired, reference intervals were established. With these results, the routine can be inserted in the routine of periodic tests, the values of baseline can be defined for the other equipment of the clinic. This determination of the equipment reference results in greater reliability in the method and, consequently, in the diagnosis resulting from it.